Gastric mucosal devitalization (GMD): translation to a novel endoscopic metabolic therapy - Fayad, Lea; Oberbach, Andreas; Schweitzer, Michael; Askin, Frederic; Voltaggio, Lysandra; Larman, Tatianna; Enderle, Markus; Hahn, Hartmut; Khashab, Mouen A.; Kalloo, Anthony N.; Kumbhari, Vivek (Endoscopy International Open, 2019)
Background and study aims The metabolic effects of bariatric surgery may partially result from removal of the gastric mucosa, an often underappreciated endocrine organ. Using argon plasma coagulation (APC), we may be able to selectively devitalize (ablate) the mucosa. The aim of this study was to identify the optimal tissue color that would correspond to selective gastric mucosal devitalization (GMD) using ex-vivo human stomach specimens.Patients and methods Stomach specimens were obtained at sleeve gastrectomy. Prior to APC application, a submucosal fluid cushion was created. APC was then applied over a 2 × 2-cm area to the fundus and body, aiming for the three indicator colors (white, golden, brown). Pathological analysis was then performed independently and in a blinded fashion by two pathologists to determine the depth of mucosal and submucosal percent thermal injury and mucosal percent cell death.Results Six patients were enrolled. There was a significant correlation between tissue color and mucosal percent thermal injury. The highest percent mucosal thermal injury was seen with brown (99.6 %, 95 % CI: 98.7, 100), followed by golden (92.5 %, 95 % CI: 85.5, 99.5), and then white (75.2 %, 95 % CI: 58.3, 92.1, P < 0.01). Submucosal thermal injury was seen in 88.9 % of the slides. Greater than minimal submucosal injury (> 10 % depth) was found significantly more with brown tissue color (91.6 %) than golden (75 %) or white (33.3 %, P < 0.05). However, 91.7 % of the entire sample set < 50 % injury.Conclusion GMD is achievable using APC without thermal injury to muscularis propria. A golden color results in sufficient mucosal injury with only superficial injury to the submucosa.